Development of the Optics Valley Photon suspended monorail train - LIU Yuwen; DING Sansan; WANG Anjun (机车电传动)
Suspended monorail trains represent an important component of urban rail transit and this mode of transportation is regarded as promising for applications in China. This paper begins with an introductory interview of the development of suspended monorail trains and subsequently analyzes the technical schemes of the Optics Valley Photon suspended monorail trains from various perspectives, including the general design, bogie system, car body system, electrical system, braking system, and network system. It further elaborates on key performance aspects such as safety, intelligence, low-carbon emissions, and environmental protection. The Optics Valley Photon suspended monorail trains have been successfully verified through simulation testing and experiments at both the component and vehicle levels. Furthermore, actual train operation on the track has demonstrated overall performance in alignment with industry application requirements.